Avaliação in vitro de biossurfactantes lipopeptídeos para o controle do crescimento e formação de biofilmes de Malassezia furfur - Silva, Gabrielly Oliveira da (2021)
Lipopeptide biosurfactants are biological molecules with low toxicity that arouse the growing interest of the pharmaceutical and cosmetic industry. Their chemical structure confers antimicrobial properties and the ability to remove and inhibit the formation of biofilms of different species of fungi and bacteria. Despite the potential of these molecules, few studies have demonstrated their action against yeasts of the Malassezia genus, which cause dermatitis and serious infections. Thus, the aim of this study was to evaluate the antifungal action of 13 lipopeptide biosurfactants produced by Bacillus sp., and their potential for removal and inhibition of biofilm formation of clinical isolates of the genus Malassezia. Strains of Bacillus sp. biosurfactant producers were grown in mineral medium for 48 h, 150 rpm, at 30 °C, and the biosurfactants purified by acid precipitation. Four clinical isolates identified as M. furfur were used in the study of antifungal activity and to determinate the Minimum Inhibitory Concentration - MIC50, using the microdilution method according to CLSI. The antifungal agents fluconazole and itraconazole were used as a positive control. As a result, six biosurfactants were able to inhibit the growth of M. furfur isolates, these being TIM10, TIM13, TIM58, TIM68, ICA24 and JAG248. The biosurfactant produced by B. subtilis TIM10 showed greater capacity for pathogens growth inhibition, showing no statistical difference compared to those obtained by the commercial antifungal fluconazole, for the M. furfur 154DR8 and M. furfur 153DR5 isolates. It was observed that at CIM50, biosurfactants TIM10, TIM13, TIM58 and TIM68 were able to remove biofilm in plaque at rates above 50%. In addition, the six biosurfactants also inhibited biofilm formation, especially TIM10 and TIM13, which inhibited it by about 90%. The toxicity of the TIM10 and TIM68 biosurfactants was tested against murine fibroblast cells, and the results demonstrated low toxicity of these lipopeptides in concentrations below 100 µg/mL. Based on these results, the biosurfactants represents promising molecules as antifungal and biofilm inhibitor against clinical isolates of M. furfur. Biosurfactants of B. subtilis TIM10 and B. vallismortis TIM68 demonstrated the greatest efficacy, in addition to their low toxicity, showing potential to compose formulations for treatment of infections caused by Malassezia sp.